In Council. Philadelphia, 28th July, 1777 : Sir, The following lines come to you from Council in the most pressing exigency of public affairs, in which the very existence of this state is threatened . - Wharton, Thomas, 1735-1778 (LLMC-digital (Series), 1777)
Circular letter to the county lieutenants, ordering the militia to be called out on the expected arrival of the British in Delaware Bay.